Mixed Integer Models for Branched Sheet Metal Products - Günther, Ute; Martin, Alexander (PAMM, Proceedings of Applied Mathematics and Mechanics, 2006)
A new technique for forming sheet metal makes it possible to construct branched sheet metal products out of one piece of sheet metal. Since the number of potential ways to produce one and the same component increases exponentially with every additional branch, appropriate tools for handling the large number of possibilities are necessary. In this paper we give a Mixed Integer Program that models the different ways of producing branched profiles and show how to incorporate manufacturing constraints into the model.